PENINGKATAN HASIL BELAJAR PENYAJIAN DATA DALAM TABEL SISWA KELAS 3 MELALUI PENERAPAN MODEL PEMBELAJARAN PJBL DENGAN PENDEKATAN DEEP LEARNING BERBASIS LINGKUNGAN - Galih Fatchan, Erist; Rosmiati; Pujantika Vatmala, Galuh; Nurfaiza, Isrina; Maria Puspitasari, Anastasya; Yulaikah, Anik; Kartika Ratri, Deby; Nurhayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve students’ learning outcomes in presenting data in table form through the implementation of the Project Based Learning (PjBL) model with a deep learning approach based on the environment. This research employed Classroom Action Research (CAR) conducted in three cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 21 third-grade students of SD Negeri Margorejo 5/407. Data were collected through learning outcome tests, observation sheets of students’ activities, and documentation. The results showed that the implementation of the Project Based Learning (PjBL) model with a deep learning approach based on the environment was able to improve students’ learning outcomes gradually. The percentage of students who achieved the high category increased from 28.57% in Cycle I to 47.62% in Cycle II, and reached 66.67% in Cycle III. Meanwhile, the percentage of students in the low category decreased from 38.10% in Cycle I to 23.81% in Cycle II, and 14.29% in Cycle III. In addition, students’ learning activities also improved, as students became more active in collecting, processing, and presenting data from their surrounding environment. Based on these findings, it can be concluded that the implementation of the Project Based Learning (PjBL) model with a deep learning approach based on the environment is effective in improving both students’ learning outcomes and engagement in learning data presentation in tables at the elementary school level.